Levels of Evidence in Small Animal Dentistry and Oral Surgery Literature Over 40 Years - Schneider, Lindsey A.; Carney, Patrick C.; Eldermire, Erin R. B.; Fiani, Nadine; Peralta, Santiago (Frontiers in Veterinary Science, 2020)
Veterinary dentistry and oral surgery are relatively new clinical disciplines that have rapidly evolved in the last few decades. Although clinical standards of care are supported by a growing body of literature, the extent to which peer-reviewed, evidence-based studies have contributed to advancing the practice of dentistry and oral surgery has not been assessed. The purpose of this study was to survey literature on the clinical practice of small animal dentistry and oral surgery published over the past 40 years to evaluate the levels of evidence over time, authorship affiliation, funding, and clinical subdisciplines within the field. A literature search was conducted in PubMed and the identified articles were screened for inclusion. A total of 1083 articles were included for final analysis. Three reviewers independently assessed and assigned each article to one of nine predetermined study design categories. Systematic reviews and meta-analyses were considered the highest level of evidence, whereas expert opinion and experimental (ex vivo, in vitro, or in silico) studies were deemed the lowest levels of evidence. For statistical analysis and interpretation, study type was dichotomized into high evidence designs from which causal inference and/or associations could be derived, and low evidence designs which were purely descriptive or non-clinical experiments. No statistically significant difference in the distribution of study type was seen over time, with the majority of research in the last 5 years being largely at high risk of bias and descriptive in nature: 80.6% of articles published between 2014-2019 were assigned to the low evidence design tier. The type of study was found to differ by author affiliation: high evidence study designs were found more often than expected when author affiliation was multi-institutional or industrial, whereas private practice authorship was underrepresented in the high evidence design tier. To meet the increasing demand for evidence-based studies on the practice of dentistry and oral surgery in dogs and cats, researchers are encouraged to consider study design when testing hypotheses to improve the quality of research.